Epidemiology of ATTRV30M neuropathy in Cyprus and the modifier effect of complement C1q on the age of disease onset. (2nd October 2018) - Andreou, Savanna; Panayiotou, Elena; Michailidou, Kyriaki; Pirpa, Panayiota; Hadjisavvas, Andreas; El Salloukh, Adonis; Barnes, Daniel; Antoniou, Antonis; Agathangelou, Petros; Papastavrou, Katia; Christodoulou, Kyproula; Tanteles, George A.; et al.
Abstract: Background: ATTRV30M amyloidosis is a lethal autosomal dominant sensorimotor and autonomic neuropathy caused by amyloid deposition composed of aggregated misfolded TTR monomers with the V30M mutation. The age of onset in patients with ATTRV30M varies in different foci and the mechanism behind it is still unknown. Methods: The tertiary neurology center following all ATTRV30M patients in Cyprus was used to collect demographic data to estimate; prevalence, incidence, penetrance, anticipation, time from disease onset to diagnosis and transplantation. Ocular, cardiac and leptomeningeal involvement in transplanted patients was explored. Correlation of C1q tagging SNPs with age of disease onset was carried out. Results: Prevalence and incidence for ATTRV30M neuropathy in Cyprus are 5.4/100, 000 and 0.3/100, 000 respectively. Mean age of onset is 40.6 years and anticipation is 8.3 years. Penetrance reaches 51% and 75% by the ages of 50 and 80 years respectively. In liver transplanted patients rates of ocular, cardiac and leptomeningeal involvement were estimated to be 60%, 20% and 16%, respectively. C1q polymorphisms correlated with age of disease onset. Conclusions: ATTRV30M neuropathy has a rising prevalence in Cyprus due to improved survival of patients. Late onset complications are becoming a major problem. Complement C1q appears to be a modifier in this disease.